Bridging the gap between HR higher education competency development and the expectations of the labour market - Raffay-Danyi, Ágnes; Bogdány, Eszter; Dabrónaki-Priszinger, Krisztina (Vezetéstudomány / Budapest Management Review, 2023)
A competency gap can be detected between the expectations of employers and the actual competencies of graduate students. Therefore, it is essential that degree programmes are based on the analysis of the competency expectations of the labour market. The study aims to assess and compare the key competencies of Human Resources bachelor educational programme requirements and employers’ expectations. The competency requirements of the labour market were mapped by analysing job adverts and by focus group interviews. The Q-methodology analysis ranked the importance of the listed competencies. A significant gap was detected between employers’ expectations and educational requirements in the case of knowledge-based competencies; similar gaps were also revealed in certain ability- and attitude-based competencies, such as assertive communication, time management, empathy and openness. The results can assist decision-makers in developing competency-based degree programmes that are better aligned with labour market expectations.